Substâncias húmicas de latossolos dos Estados de Minas Gerais e Pará - Villani Longo , Jacqueline; Fernandes , Bairon; Alves Moreira, Maurílio; Resende , Mauro; Gomide Loures , Emílio (Revista Ceres, 2025)
Some aspects of soil organic matter were studied in soils from two regions (Viçosa and Turmalina) of Minas Gerais State, and one region (Itaituba) of Pará State.